1994
DOI: 10.1161/01.str.25.12.2492
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of fibromuscular dysplasia and cystic medial necrosis in a patient with Marfan's syndrome and bilateral carotid artery dissections.

Abstract: A primary arteriopathy is suspected in most patients with spontaneous dissections of the carotid artery, although the nature of this arteriopathy usually remains elusive. Angiographic changes of fibromuscular dysplasia (FMD), however, are found in 10% to 20% of patients with carotid dissections. A 26-year-old woman with Marfan's syndrome presented with bilateral amaurosis fugax after surgical repair of an aortic dissection. Angiography revealed a dissection extending from the ascending aorta into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
54
0
7

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(63 citation statements)
references
References 30 publications
2
54
0
7
Order By: Relevance
“…Arterial dissections may occur as complications of FMD 14 and are likely to be related to vessel wall frailty. Coexistence of FMD and connective tissue disorders has been reported and it has been suggested that FMD might be a nonspecific manifestation of such disorders 18 . The patient did not have signs of connective tissue disease but this diagnosis could not be completely ruled out.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Arterial dissections may occur as complications of FMD 14 and are likely to be related to vessel wall frailty. Coexistence of FMD and connective tissue disorders has been reported and it has been suggested that FMD might be a nonspecific manifestation of such disorders 18 . The patient did not have signs of connective tissue disease but this diagnosis could not be completely ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…Injection of elastase into the media of the carotid artery has been associated with development of dilatations and elongations of the injected vessels in rabbits 17 . Miscellaneous conditions linked with arterial media involvement have been diagnosed in association with dilatative arteriopathy: FMD 13,14,16,18 , giant cell arteritis 19 , Anderson-Fabry disease 20 , von Recklinghausen's disease 21 , alpha-glucosidase deficiency 22 , alpha-1 antitrypsin deficiency 23 , and connective tissue disorders such as Marfan's syndrome 18,24 . Mechanical instability and loss of elasticity might predispose to dissection or distention at points of minor resistance in the arteries of affected patients.…”
Section: Casementioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the effect of pregnancy on the symptoms in PAPA syndrome needs further investigation. There are few published cases of cerebral arterial dissection even in hereditary connective tissue diseases during pregnancy (e.g., Ehlers–Danlos syndrome and Marfan syndrome) 5, 6. Mizutani reported that cerebral arterial dissection has a low frequency of causing SAH (3.2%) 7.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple simultaneous arterial dissections may occur, especially with the presence of an elastic-tissue disease, such as fibromuscular dysplasia, pseudoxanthoma elasticum, or Ehlers-Danlos or Marfan syndrome. 4,5 In addition to these well-defined diseases, the presence of multiple arterial involvement suggests the existence of a transient arteriopathy: the underlying pathological condition may be due to the association of abnormalities of the extracellular matrix, with a possible inflammatory trigger. 5,6 Ischemic cerebral complications include cranial nerve paralysis in Ͼ10% of the cases 1 : lower cranial nerve palsies seem to occur in about 5% of the cases and almost invariably involve cranial nerve XII, with or without the additional involvement of other lower cranial nerves (IX, X, and XI).…”
Section: Discussionmentioning
confidence: 99%